METACOGNITIVE ABILITY EMPOWERMENT AS A MEANS OF DEVELOPING LEARNERS’ CHARACTERS - Ika Mustika (International Conference on Languages and Arts, 2014)
The shifting of era to severe globalization may lead to the fading of one’s character especially learners as youth who are vunerable to this issue. School as formal education institution is a powerful means in the process of learners’ character formation in addition to family. School as the learners’ second home after family must be able to provide adequate practice of character education so that it can produce youth generation who have not only intellectual intelligence but also emotion and spiritual intelligences. Those three shall create a characterized youth of nation. In realization, it means implementing character education through the process of learning. In this case, it needs teacher’s ability to plan and conduct the learning process leading to the process of learners’ character formation.One of the ways that can be done is by empowering metacognitive ability. The empowerment of metacognitive ability may be conducted by teaching the learners to use metacognitive strategy. By empowering metacognitive ability, learners are expected to get used to always monitor, control, and evaluate their learning comprehension. This ability is essential to be mastered thus the learners can have responsibility of their own learning. Being responsible is a basic value which is universally recognized that learners should have. In conclusion, this basic value is the benchmark of the learners to behave and act in accordance with moral code. This is beneficial to live their lives in the future.   Keywords: Metacogntive Ability, Character Development